Analisis Pengaruh Kualitas Website Terhadap Kepuasan Pengguna Pada Website Perpustakaan Institut Bisnis Dan Informatika Stikom Surabaya - Fajjrul Junaidi; Sulistiowati Sulistiowati; Sri Hariani Eko W (Jurnal Sistem Informasi Universitas Dinamika, 2017)
Library Institut Bisnis dan Informatika Stikom Surabaya as part of Institu Bisnis dan Informatika Stikom Surabaya utilizing website to provide information quickly and easily to the user library. As long as this has not been done in the implementation of evaluation about website quality based on perception en user as a feedback to website management so that the user be satisfied against services.Based on analysis problems of relation between website quality and customer satisfaction. From dissemination of questionnaires conducted to end user website retrieved samples as many as 70 respondents. Data from the results questionnaire done testing variable with test validity and reliability. Next do a test data and test normality assumption as a condition for the next step, namely the multiple linear regression analysis.The results of test are obtained that the variable include usability, information quality and interaction quality a positive and significant effect against customer satisfaction.